Effect of Xylanase on Performance and Apparent Metabolisable Energy in Starter Broilers Fed Diets Containing One Maize Variety Harvested in Different Regions of China - H. V. Masey O’Neill (Asian-Australasian Journal of Animal Sciences, 2012)
The objective of this study was to investigate the variability in broiler performance, apparent metabolisable energy (AME) and ileal digestible energy (IDE) between five different maize samples fed with and without xylanase at 16,000 U/kg. Various in vitro characterisations were conducted to determine if any could predict performance or AME. Samples of the maize were harvested in five diverse regions and fed individually in a mash diet as follows (g/kg): test maize 608.3; soya bean meal (SBM) 324.1; poultry fat 25.2; salt 4.6; met 2.6; lys 1.6; thr 0.5; limestone 9.7, dical 18.4; vit/min 5.0; CP 210 and ME (kcal/kg) 3,085. The diets were fed to 720 broilers with 6 replicates, each containing 12 birds per treatment, from 0 to 18 d of age. Maize samples were analysed for starch, protein, crude fibre, fat, protein solubility index (PSI) and vitreousness using near infra red reflectance spectroscopy (NIR). They were also assayed using an in vitro starch digestibility method. The results showed that there was no effect of harvest region on the feed intake (FI), body weight gain (BWG) or feed conversion ratio (FCR) of the broilers over the 18 d period (p = 0.959, 0.926, 0.819 respectively). There was an improvement in all parameters with the addition of xylanase (FI p = 0.011; BWG and FCR p<0.001). There was a significant positive effect of xylanase on IDE, AME, IDE Intake (IDEI) and AME intake (AMEI) (p<0.0001 in all cases). Although there was no significant effect of maize source, there was a strong trend towards variability in IDE (p = 0.066) and AME (p = 0.058). There were no significant correlations (p<0.05) between any proximate or physiochemical values and any performance or AME values. This may suggest that none of those selected were suitable predictors for performance or AME. The broilers performed well according to the breed guidelines, with slightly increased FI, increased BWG and similar FCR prior to the addition of xylanase. When FCR and BWG were analysed with FI as a covariate, xylanase addition remained significant suggesting that the improvement in BWG and FCR was driven by an increase in digestibility and nutrient availability.